Implementasi Kurikulum Program Magang 24 Minggu dalam Upaya Peningkatan Kapasitas Pengetahuan di Ruang Belajar Aqil Kota Malang - Sawitri, Depikke Nurcholisya; Riyanto, Yatim (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2023)
Based on data presented by the Central Statistics Agency (2022) regarding youth, as many as 30.38% are part of NEET. One way to reduce this is by involving students in internship programs. One of the institutions that runs and provides internship programs is the Aqil Learning Room. Aqil Learning Room needs to develop a program curriculum to design goals, achievements, content, assessment and program evaluation. This research uses qualitative methods and is presented descriptively. The results of this research are that the implementation of the curriculum is good. The capacity increases experienced by participants are changes in skills, changes in the learning process, knowledge management, and increased abilities. Supporting factors for implementing the curriculum are that participants are accompanied by relevant mentors, there are coaching sessions for participants that are tailored to the project tasks being carried out, there are volunteer development sessions that help participants to develop themselves after the program ends, and there is monitoring of results and mapping of the impact of participants' learning during participation. 24 Week Internship program at Aqil Study Room.